Analisis Potensi Likuifaksi Berdasarkan Data Cone Penetration Test (Studi Kasus Belawan, Medan) - Sari, Siti Nur Indah; Bintang, Rajinda (Universitas Andalas, 2023)
One of the impacts of an earthquake is liquefaction. If an earthquake with a large magnitude occurs in an area, it can destroy facilities and infrastructure, then it is possible that the next impact will be liquefaction. Moreover, the buildings are located not far from the beach, because of the characteristics of the sandy soil which has a high friction angle like in the Belawan area, Medan City. And from the analysis of liquefaction potential based on CPT (Cone Penetration Test) data, as well as calculations and analysis of physical soil data, earthquake magnitude and CSR and CRR cyclic loads at six drilling points carried out in the area, it was found that the land at the location experienced potential liquefaction because the safety factor is < 1. Which is influenced by the CSR (cyclic stress ratio) value and the CRR (cyclic resistance ratio) value which is very small, as well as the assumption that the earthquake acceleration is 7.5 SR with an amax value of 196.94 gal.